Learning from marketing: Rapid development of medication messages that engage patients. Issue 8 (August 2015) - Yank, Veronica; Tribett, Erika; Green, Lydia; Pettis, Jasmine
Highlights We adapted marketing approaches to develop advertising-style messages for patients. The partnership with marketing experts was efficient, rapid, and fairly inexpensive. Resulting messages were likely to motivate patients to seek recommended medications. The messages and general approach were acceptable to both patients and providers. We explain key elements of our partnership and process to help others replicate them.